Evidence on the Employer Size-Wage Premium from Worker-Establishment Matched Data - Troske, Kenneth R. (The Review of Economics and Statistics, 1999)
In spite of the large and growing importance of the employer size-wage premium, previous attempts to account for this premium using observable worker or employer characteristics have had limited success. The problem is that, while most theoretical explanations for the size-wage premium are based on the matching of employers and employees, previous empirical work has relied on either worker surveys with little information about the employer, or establishment surveys with little information about the workers. In contrast, this study uses the newly created Worker-Establishment Characteristic Database, which contains linked employer-employee data for a large sample of U.S. manufacturing workers and establishments, to examine seven explanations for the employer size-wage premium. A number of the explanations can account for some of the observed cross-sectional variation in worker wages. However, none of the explanations can fully account for the employer size-wage premium. In the end there remains a large, significant, and unexplained premium paid to workers of large employers.